ANALISIS KEUNGGULAN KOMPETITIF DAN SPESIALISASI SEKTOREKONOMI DI KABUPATEN BLORA TAHUN 2011-2015 - ARYADIPURA, DICKY; , Dr. Daryono Soebagyo.,MEc (2017)
This study aims to determine the superior sector whatever is in Blora and determine what the leading sectors in use as a specialization of economic sectors in the district Blora 2011-2015. This study uses secondary data is data GDP in Blora and Central Java Province. In this study will be used tools Location Quotient, Shift-Share-Marquilas Esteban. Based on the analysis LQ for the period 2011-2015, the potential winning Blora regency is dominated by agriculture, forestry and fisheries; mining and quarrying; sectors of wholesale and retail trade, repair of cars and motorcycles; sector provision of accommodation and eating and drinking; sectors of government administration, defense and compulsory social security; educational services sector; sector health services and social activities; the services sector; and the last is the service sector laiinnya. Determining the sector specialization used second analysis is shift-share esteban marquillas seen from the Aij (allocative effect), the average value of Aij 2011-2015 showed that Blora has been specializing in mining and quarrying; sectors of wholesale and retail trade, repair of cars and motorcycles; sector provision of accommodation and eating and drinking; insurance and financial services sector; sectors of government administration, defense and compulsory social security; educational services sector; sector health services and social activities; and other